Nursing Care of Patients With Ineffective Airway Clearance Problems - Mustopa Saepul Alamsah; Tasya Azahra; Egi Mulyadi (Institute of Computer Science (IOCS), 2022)
Bronchial asthma is a condition in which the airways narrow due to hypersensitivity to certain stimuli, which causes inflammation. Eucalyptus is a plant that is often used as a drug by inhalation because it contains terpenes, porphyrin derivatives, and other phenolic compounds for pharmacological activity. Eucalyptus can be inhaled to produce local or systemic effects through inhalation by inhalation using a vapor, nebulizer, or aerosol spray. This study aims to carry out nursing assessments for clients who experience asthma, establish nursing diagnoses for clients who experience asthma, develop nursing plans for clients who experience asthma, carry out nursing actions for clients who experience asthma, carry out nursing evaluations for clients who experience asthma, perform discussion of the results of the application of eucalyptus aromatherapy to clients who experience asthma. The research method was carried out qualitatively with a content analysis approach to patients directly. The results obtained prove that there is an effective effect in administering simple steam aromatherapy eucalyptus inhalation therapy to asthma sufferers.